Urban green space growth impact on surface temperature distribution / Siti Nor Afzan Buyadi, Wan Mohd Naim Wan Mohd and Alamah Misni. - Buyadi, Siti Nor Afzan; Wan Mohd, Wan Mohd Naim; Misni, Alamah (Universiti Teknologi MARA Cawangan Selangor, 2018)
Trees and vegetation play a vital role to mitigate urban heat island (UHI) effects. Land use, vegetation growth detection and land surface temperature (LST) maps of two different dates are generated from Landsat 5 TM (1991 and 2009) in the city of Shah Alam. The conversion of natural green areas into residential and commercial development significantly increases the LST. The result reveals that mature trees in urban green space help to mitigate the effects of UHI as well as to sustain the urban development.